The Effect of Organizational Learning, Organizational Culture and Innovation in Project Performance of PT. PLN (Persero) - Alfionita, Ajrina; Syairudin, Bambang; Ma’ruf, Buana (IPTEK Journal of Proceedings Series, 2019)
Business challenges involving external and internal problems occur within the attempts made by PT. PLN (Persero) in providing electricity services and in completing the 35.000 MW electricity project. External problems are related to Holder of Electricity Service Business Permit or Pemegang Usaha Penyediaan Tenaga Listrik (PIUPTL) that has opened this business as a non-monopolistic business. Meanwhile, internal problems include inadequate number of employees and imbalance proportion of employees who are retiring shortly. Those issues demand the company to guarantee that all organizational knowledge is well-documented before the retirement, regeneration and employee placement. In addition, the competence of employees and structural staffs should be improved. These attempts have to be administered to utilize the knowledge owned by the company to drive new innovations in order to improve the services given to customers and to improve the corporate performance. The building of new power plants and transmissions should be well-anticipated by PT. PLN (Persero) Unit Induk Distribusi that hold the responsibility related to the quality of electricity distribution. In order to run those roles, it is necessary to determine clear target of Action Plan and Company Budget for new projects, infrastructure maintenance for electricity distribution to avoid energy not sales. The success of company projects is measured by several parameters including time, quality and costs. The success of those project can be achieved through good innovation, organizational culture and organizational learning that have been empirically validated in prior research. However, research on the simultaneous influence of those three variables on the success of a project especially on the utility aspect has not yet been conducted. This research was conducted to investigate variables that were assumed to have significant influence on project performance including organization learning, organizational culture and innovation. This research involved 75 unit managers of Unit Pelaksana Pelayanan Pelanggan in all Unit Induk Distribusi all over Indonesia. In this research, the Structural Equation Modelling (SEM) was used in data validation and data analysis. The results of this research showed that Organizational Culture had a significant and positive influence on Project Performance. Meanwhile, Organizational Learning was found to have a positive and significant influence on Innovation. Those findings are expected to provide valuable insights for the company management in designing work programs to improve Organizational Culture and Organizational Learning